Locating Leadership of Art in UK Primary Schools - Gregory, Peter (Revija za elementarno izobraževanje, 2017)
Using some of the evidence collected as part of a doctoral study of school-based leaders of art in the UK, this paper presents the most recent and emergent models of the leadership in art. The data suggests likely attributes of those in leadership positions and the effects upon the activities in which those individuals engage. As a case study of over two hundred art leaders, the challenges are clearly presented. They are more deeply explored through interviews and discussions about attitudes to artworks and their use with learners in the classroom as well as by analysing the paper records kept by the leaders. The study raises important issues for those who might want to learn from the situation in the UK.